Micro-encapsulation of fruit extracts for food applications: An innovative approach - Singh, Ningthoujam Samarendra; Singh, Akath; Khilladi, Bharati; Rastogi, Dheerendra (Indian Horticulture, 2026)
Fruit extracts are rich in bioactive compounds such as polyphenols, carotenoids, flavonoids, and vitamins, which offer significant health benefits. However, their direct incorporation into food systems is limited by low stability, poor solubility, and susceptibility to degradation during processing and storage. Microencapsulation and bigel technologies have emerged as effective strategies to overcome these challenges by enhancing compound stability, bioavailability, and controlled release. Microencapsulation and bigel systems using fruit extracts, particularly mangiferin from mango and anthocyanins from jamun, have been standardized at ICAR-CISH Lucknow. Extraction, stabilization protocols, and wall material interactions were optimized to preserve color, phytochemical content, and sensory properties. These innovations enable the development of value-added, fruit-based functional foods with improved stability, enhanced health benefits, and greater consumer appeal, contributing to healthier and market-ready food products.